Developing the Potential of Islamic Boarding Schools Through RAS Method Fish Farming - Alfia, Yulis Diana; Setiyawati, Hari; Suharmadi, Suharmadi; Widyanto, Muhammad Laras; Hadnan, Muhamad; Choiriah, Siti; Pratiwi, Riri; Surjandari, Dwi Asih; Marlina, Rini; Mubarakah, Septyana; Utami, Siska Widia; Rahayu, Puji; Suroso, Edy (Universitas Muhammadiyah Sidoarjo, 2025)
Islamic boarding schools have great potential which requires support for its development. The purpose of this community service program is to provide counseling, training and practice of fish farming for teachers, management, and students of class XII SMA-IT Riyadhussholihiin. This program uses the Asset-Based Community Development (ABCD) approach to explore the potential to meet the requirements of the institution more optimally, independently, and sustainably through the entrepreneurial development of fish farming using RAS (Recirculating Aquaculture System) method. Potentiality exploration (strengths/assets/capital), opportunities, and aspirations is carried out, so that appropriate results can be achieved. The potential resources identified are intangible, such as systems, cohesion, experience, and quality of human resources; and tangible such as land, human resources, and nature. These potential assets form the basis for program development. The results of the program are explained using Actor Theory. Based on the theory, the program can encourage the improvisation of the institution as an actor, increasing the use of existing resources, through the provision of self-food supply. The sustainability of the program is expected to be achieved through entrepreneurial life-skill education for all potential human resources, fish farming can also be increased in production to be marketed. Highligts: Community Empowerment: The program focuses on empowering teachers, management, and students through fish farming practices. ABCD Approach: The Asset-Based Community Development method explores strengths, resources, and aspirations for sustainable development. Entrepreneurial Life-Skills: The initiative promotes self-sustainability by educating participants on entrepreneurial fish farming. Keywords: Islamic boarding school, fish farming, entrepreneurship, asset-based community development, actor theory